ENTOMOLOGICAL, DINAMIC MODEL FOR ESTIMATING INTERNVAL POST- MORTEM - Noverta Indriyansyah, Deri
The indetification of the postPost) mortem interval begins when the body is found. The main question is to identify the time of death. In reality, this task is complicated because of the many local factors involved in th e decay process. In many cases, the decomposition process is carried out by certain local insects that consume the whole biomass. In this study, we will discuss how to model postinvolving diptera with rabbits as biomass. According to the mortem intervals data and numerical simulations, it is shown that the dynamics of the interaction between diptera and biomass formulate a type of logistic model with carrying capacity that decomposes only with Diptera. The postmortem interval is shown as the period at the end of consumption when the larvae have completely consumed the biomass. From the simulation, it can be seen that the decomposition lasted for 176 hours.